Implementasi Range of Motion (ROM) terhadap Kemampuan Mobilisasi pada Ibu Post Sectio Caesarea di Ruang Mawar RSUD KardinahKota Tegal - Uswatun Insani; Rifdah Aulia Zuhriyyah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Caesarean section (CS) is a major surgical procedure that can limit early mobilization in postpartum mothers due to pain and restricted movement. Early mobilization is essential to prevent complications such as thromboembolism and to support the healing process. One effective non-pharmacological intervention to improve mobilization is Range of Motion (ROM) exercises, which aim to maintain joint flexibility, enhance muscle strength, and improve blood circulation. This study used a descriptive case study design with an analytical approach involving two postpartum mothers who had undergone caesarean section and met the inclusion criteria. ROM exercises were administered once daily for three consecutive days. Data were collected through interviews, physical examinations, direct observation, and medical record review. Mobilization ability was evaluated based on four aspects: repositioning in bed, moving from lying to sitting, sitting to standing, and transferring from bed to chair. The results showed that both patients experienced significant improvements in mobilization ability after the ROM intervention. On the first day, movement was limited; however, by the third day, patients were able to sit, stand, and transfer independently. Muscle strength, particularly in the lower extremities, also improved. The gradual application of active ROM exercises proved effective in reducing pain, increasing muscle strength, and accelerating recovery. Psychological support, patient education, and active participation further supported the intervention’s success. The study concludes that ROM exercises are effective in enhancing mobilization among post-caesarean section mothers and should be routinely initiated six hours after surgery to promote recovery and prevent immobility-related complications.